The Impact of Brawls on Youth Morality in Tegal - Putri, Hany Lidya (Journal of Linguistics and Social Studies, 2025)
Juvenile delinquency includes behaviour that deviates from the norms of criminal law committed by adolescents. Such as brawls, bullying, motorbike gangs, and drugs. Many factors that cause juvenile delinquency need to be considered, especially this brawl which has several factors. The negative impact caused by this brawl action. The purpose of this study is to determine the causal factors and the impact of brawls on adolescent morality. This research uses a qualitative method. By collecting data from interviews, and various sources from journals. The results of this study indicate that there are factors, impacts, and solutions or efforts for the brawl action. The impact of brawls that cause moral decline in adolescents, where a decrease in one's character in various aspects. So that the role of parents and families in shaping children's character is needed. Because it is in the family that children get education for the first time, it is very important that parents instil moral education early on. It is not only schools that have the responsibility for children's moral education, but parents must also take responsibility.